3g, 4g and beyond : bringing networks, devices and the web together - Sauter, Martin (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
Extensively updated evaluation of current and future network technologies, applications and devices This book follows on from its successful predecessor with an introduction to next generation network technologies, mobile devices, voice and multimedia services and the mobile web 2.0.
Includes index.
Keywords: LONG-TERM EVOLUTION (TELECOMMUNICATIONS)